KERAGAMAN JENIS DAN PREFERENSI EKOLOGI BEGONIA LIAR DI KAWASAN REMNANT FOREST KEBUN RAYA CIBODAS - Muhammad Efendi; Nur Azizah; Ateng Supriyatna; Destri Destri (BERITA BIOLOGI, 2017)
Wild species of begonia existed in remnant forest of Cibodas Botanic Gardens, but their diversity, distribution and ecological preference were not much known. Data of condition and habitat characteristic of wild begonia are important in their cultivation. The aims of this study are to inventory the diversity of wild begonias and their distribution habitat preference in remnant forest of Cibodas Botanic Gardens. Sample were collected from four remnant forest using exploration method. Analysis of vegetation where wild Begonia existed was conducted using 1x1 m plot in around every individu of Begonia found. The principle component analysis (PCA) was carried out using R program version 2.11.0. The result showed that 50% of the mountain Begonia in West Java can be found in remnat forest area. The light intencity, soil humidity and air humidity were highly correlated to distribution of wild Begonia. The microclimate conditions in remnant forest area are appropriate with habitat of Begonia.